Tantangan dan Peluang Pesantren di Tengah Masyarakat Non Muslim Studi di Pondok Pesantren Bali Bina Insani - Khairani, Eka Zahrina; Riyadi, Dimas; Hadyansyah, Arkan; Setyawan, M. Adin (Universitas Nurul Jadid, 2025)
Pesantren is an Islamic educational institution that has an important role in shaping the character of society. However, the existence of pesantren in a non-Muslim majority society, such as Pondok Pesantren Bani Insani in Bali, presents unique challenges and opportunities. This research aims to understand the pesantren's adaptation strategy in creating social harmony while maintaining Islamic values. With a qualitative approach, this research uses a case study through in-depth interviews, direct observation, and document analysis to obtain a comprehensive picture. The results showed that Bani Insani Islamic Boarding School faced challenges in the form of religious stereotypes, limited resources, and social and cultural complexity. Nevertheless, this pesantren is able to take advantage of opportunities through the implementation of inclusive education, interfaith dialogue, and empowerment of the local community. These results emphasize the importance of adaptive strategies and cooperation to strengthen the role of pesantren as unifiers in the midst of community diversity.